Free‐electron concentration and polarity inversion domains in plasmonic (Zn, Ga)O. Issue 3 (5th December 2014) - Sadofev, Sergey; Kalusniak, Sascha; Schäfer, Peter; Kirmse, Holm; Henneberger, Fritz
Abstract Heavily Ga‐doped ZnO layers are grown on bulk ZnO wafers by molecular beam epitaxy. The layers grow in a two‐dimensional pseudomorphic mode with high structural quality under increase of the c‐lattice constant up to free‐electron concentrations of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj984f4fw" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />1021</alternatives>cm<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj984f4hx" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />−3</alternatives>. Formation of Zn‐polar inversion domains in the O‐polar ZnO matrix is identified as the limiting factor for the incorporation of electrically active Ga. The domain formation can be inhibited by growing with larger excess of Zn. This results in a shift of surface plasmon frequency of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj984f4gd" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />ℏΔω=100</alternatives> meV and allows for covering the telecommunication wavelength range.